Vinyl chloride oligomers: On the road to understand the potential toxicity of PVC nanoplastics - Esperanza Quevedo; Emiliano Perez-Sanchez; Alexis Caballero; Ana Martinez (PLoS ONE, 2026)
On the road to understand the toxicity of nanoplastics, it is important to determine their capacity to interact with other molecules, as this is the first condition that must be met. In particular, polyvinyl chloride (PVC) is a versatile plastic widely used in construction. It can be degraded producing micro and nanoplastics, which can be formed when PVC pipes are cut during the manufacturing of products. PVC is considered to be one of the most toxic plastics, so it is important to analyze potential detrimental effects. This is the main aim of this research. On the basis of Density Functional Theory calculations, we investigated different vinyl chloride oligomers (as models of PVC nanoplastics). Degradation energies, electron donor acceptor capacities to analyze possible oxidation reactions, and interaction energies with different molecules were calculated. The vinyl chloride oligomers used in this investigation are saturated and monounsaturated. This is important since monounsaturated variant is dominant in experimental conditions. We found that none of the oligomers are good electron donors or acceptors. We also investigated different oligomers interacting with ciprofloxacin and •OOH. The interaction energies with ciprofloxacin and •OOH are negative or less than 13 kcal/mol, indicating weak interactions. This theoretical investigation indicates that vinyl chloride oligomers are not expected to be reactive or toxic, considering the electron transfer and the interaction energies with other molecules.